Menerapkan Model CLSTAD Untuk Meningkatkan Hasil Belajar Pada Mata Pelajaran Produk Kreatif Dan Kewirausahaan Kelas XI Pemasaran 1 Tahun Pelajaran 2018/2019 - Yanti Agus (Universitas Negeri Makassar, 2021)
This study aims to 1) determine the improvement of learning outcomes by applying the CLSTAD Learning model in Creative Products and Entrepreneurship Class XI Marketing 1 Academic Year 2018/2019. The research method used is classroom action research with the number of respondents as many as 36 students. The results showed an increase in learning outcomes from cycle I to cycle II. In the first cycle of student learning outcomes, has obtained a class average of 79 then an increase in the second cycle increased to 90.11. Students who completed before the action 27 students in cycle 1 and increased by 36 students in cycle 2. The highest score before action 80 increased in cycle 1 by 90 and in cycle 2 increased to 100 (highest score), while cycle 1 was 70 and in cycle 2 2 increases to 80.